The expositor's Bible commentary ; v. 9 - Gaebelein, Frank Ely, 1899-1983; Tenney, Merrill Chapin, 1904-1985; Longenecker, Richard Norman, 1930- (Grand Rapids, MI Zondervan, 1981)
Contents : v. 9 : The gospel of John / Merrill C. Tenney; The Acts of the Apostles / Richard N. Longenecker. Includes bibliographical references.
Keywords: Bible. N.T. John -- commentaries; Bible. N.T. Acts -- commentaries